2021
DOI: 10.3390/su13074073
|View full text |Cite
|
Sign up to set email alerts
|

Combined Citric Acid and Glutathione Augments Lead (Pb) Stress Tolerance and Phytoremediation of Castorbean through Antioxidant Machinery and Pb Uptake

Abstract: Lead (Pb) is one of the most toxic elements on earth. The main origins of Pb pollution are automobiles, paint and electroplating industries. Pb-induced stress has very toxic effects on plant growth and biomass. The concentration of reactive oxygen species (ROS) in plant cells significantly increases under Pb stress, which interrupts the biochemical cycles in cells and leads to cell death. Therefore, it is essential to clean up the Pb-polluted soils. Among all techniques that are used to clean soil that is meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…Stimulating impacts of SNE were noticeable owing to the existence of citric acid (CA), ascorbic acid (AsA) and proline (as antioxidants) and some micro and macronutrients (Fe, iron; Zn, zinc; Mg, magnesium) in the plant extract (Table 1). Study of Zeng et al (2021) on castor bean proved that foliar sprayed citric acid alleviated lead (Pb) stress via improving growth, as well as fresh and dry biomass. Also, a study of Zhang et al (2019) on Cd-stressed maize plants revealed that AsA application induced growth improvement via stimulation in photosynthetic pigments, amino acids, and protein, which might have enhanced cell enlargement and growth of plant (Aziz et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Stimulating impacts of SNE were noticeable owing to the existence of citric acid (CA), ascorbic acid (AsA) and proline (as antioxidants) and some micro and macronutrients (Fe, iron; Zn, zinc; Mg, magnesium) in the plant extract (Table 1). Study of Zeng et al (2021) on castor bean proved that foliar sprayed citric acid alleviated lead (Pb) stress via improving growth, as well as fresh and dry biomass. Also, a study of Zhang et al (2019) on Cd-stressed maize plants revealed that AsA application induced growth improvement via stimulation in photosynthetic pigments, amino acids, and protein, which might have enhanced cell enlargement and growth of plant (Aziz et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…CA is the initial intermediate of the TCA cycle. It plays a vital role as a mild antioxidant and metal chelation agent that interacts effectively with HMs to facilitate their immobilization, which alleviates the HM-induced stress on plants ( Godoy et al, 2021 ; Zeng et al, 2021 ). Recently, Zeng et al (2021) investigated the effects of combined application of GSH and CA on castor bean ( Ricinus communis L.) plants and demonstrated successful results in alleviating Pb-induced stress.…”
Section: Sequenced or Combined Application Of Gsh And Bioactive(s)mentioning
confidence: 99%
“…It plays a vital role as a mild antioxidant and metal chelation agent that interacts effectively with HMs to facilitate their immobilization, which alleviates the HM-induced stress on plants ( Godoy et al, 2021 ; Zeng et al, 2021 ). Recently, Zeng et al (2021) investigated the effects of combined application of GSH and CA on castor bean ( Ricinus communis L.) plants and demonstrated successful results in alleviating Pb-induced stress. The synergistic effects of GSH and CA are shown through the improved growth parameters such as length, dry weight of shoots and roots, number of leaves per plant and leaf area in Pb-stressed plants.…”
Section: Sequenced or Combined Application Of Gsh And Bioactive(s)mentioning
confidence: 99%
See 2 more Smart Citations